Challenges of Early Modern Diplomacy - Jonas Bechtold (Theatrum Historiae)
A Diet was an assembly of the Estates of the Holy Roman Empire, summoned by the Emperor to deliberate on political and judicial matters. As a multilateral forum of deliberation and communication within the Holy Roman Empire, Emperors, and Estates, Diets also attracted the attention of foreign princes, who thus sent their envoys to these Estate assemblies. Because of the variety and quantity of these foreign envoys, Diets developed into specific multilateral spaces of early modern diplomacy. The formal exclusion of the envoys from the Diets’ negotiations and meetings built up challenges and required strategies of “diplomatic” communication beyond the formal process. By comparing two envoys sent by Queen Elizabeth I (1558–1603), Christopher Mundt (1559/1566) and George Gilpin (1582), this paper shows what impact dispositive factors, such as expertise or confessional inclination, could have on an envoy’s status, his recognition by hostile and allied partners, and his assertiveness at a Diet. Furthermore, these factors mainly influenced and drove cooperation and conflict between England and the Habsburg Emperors and the Imperial Estates, and so contribute to further understanding ‘diplomatic relations’ in the 16th century.